Respuesta :
2x - 3y = -24
x+ 6y = 18
you solve the first one by the x:
2x = -24 + 3y
x = (-24+3y)/2
then you substitute what you found in the other equation and you solve by y
(-24+3y)/2 + 6y = 18 multiply everything by 2
-24 + 3y + 12y = 36
3y + 12y = 36 + 24
15y = 60
y = 60/15
y = 4
Good job! You found your y! :D
Now let's substitute the y in the first equation with 4:
2x - 3(4) = -24
2x - 12 = -24
2x = -24 + 12
2x = -12
x = -12/2
x= -6
Done!! ;)
x+ 6y = 18
you solve the first one by the x:
2x = -24 + 3y
x = (-24+3y)/2
then you substitute what you found in the other equation and you solve by y
(-24+3y)/2 + 6y = 18 multiply everything by 2
-24 + 3y + 12y = 36
3y + 12y = 36 + 24
15y = 60
y = 60/15
y = 4
Good job! You found your y! :D
Now let's substitute the y in the first equation with 4:
2x - 3(4) = -24
2x - 12 = -24
2x = -24 + 12
2x = -12
x = -12/2
x= -6
Done!! ;)
first solve for x in the second equation (x=-6y+18).then substitute -6y+18 in the first equation and solve for y.after solving for y then substitute it in one of the equation and then solve for x.
2x-3y=-25
x+6y=18
x=-6y+18
2(-6y+18)-3y=-24
-12y+36-3y=-24
-15y+36=-24
-15y=-24-36
-15y=-60
y=4
x+6(4)=18
x+24=18
x=18-24
x=-6
y=4,x=-6
2x-3y=-25
x+6y=18
x=-6y+18
2(-6y+18)-3y=-24
-12y+36-3y=-24
-15y+36=-24
-15y=-24-36
-15y=-60
y=4
x+6(4)=18
x+24=18
x=18-24
x=-6
y=4,x=-6